Especialização produtiva e vulnerabilidade territorial na Região Sucroenergética do Triângulo Mineiro, Minas Gerais - Teodoro, Marcelo Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Este trabalho teve como objetivo principal analisar a vulnerabilidade territorial decorrente do processo de especialização produtiva do setor sucroenergético na Região Sucroenergética do Triângulo Mineiro, Minas Gerais, a partir da década de 2000. Partimos da hipótese que a formação de uma região sucroenergética promove o aprofundamento da especialização produtiva resultando em maior vulnerabilidade territorial. Entende-se por vulnerabilidade territorial, a fragilização espacial decorrente da especialização produtiva que, por um lado, confere atributos de competitividade diferenciados ao segmento hegemônico, enquanto, por outro, diminui a autonomia local, à medida que insere a região num contexto de produção global, dentro do qual ela se torna funcional e alienada. Os resultados elucidaram que a Região Sucroenergética do Triângulo Mineiro se especializou no setor sucroenergético no início do século XXI, processo percebido não só no campo, mas também nas áreas urbanas com objetos técnicos e informacionais funcionais ao setor. Conforme a região foi se tornando especializada no setor sucroenergético, os processos de vulnerabilidade ficaram evidentes, tais como: a queda de outras culturas agrícolas destinadas à produção de alimentos; a área agricultável passou a ser ocupada com 40% com a cana-de-açúcar; falências e recuperações judiciais de usinas sucroenergéticas e a degradação da remuneração e queda do número de trabalhadores do setor sucroenergético.

The main objective of this work was to analyze the territorial vulnerability resulting from the process of productive specialization of the sugar-energy sector in the Sugar- energy Region of Triângulo Mineiro, Minas Gerais, starting in the 2000s. Guided by the hypothesis that the formation of a sugar-energy region promotes the deepening of the productive specialization resulting in greater territorial vulnerability. Territorial vulnerability is understood as the spatial fragility resulting from productive specialization that, on the one hand, confers differentiated attributes of competitiveness to the hegemonic segment, while, on the other hand, reduces local autonomy, as it inserts the region into a context of global production. , within which it becomes functional and alienated. The results elucidated that the Sugar-energy Region of Triângulo Mineiro specialized in the sugar-energy sector at the beginning of the 21st century, a process perceived not only in the countryside, but also in urban areas with technical and informational objects functional to the sector. As the region became specialized in the sugar-energy sector, vulnerability processes became evident, such as: the decline of other agricultural crops intended for food production; the arable area started to be occupied by 40% with sugar cane; bankruptcies and judicial recovery of sugar-energy plants and the degradation of remuneration and drop in the number of workers in the sugar-energy sector.
Productive specialization and territorial vulnerability in the Sugar-Energy Region of Triângulo Mineiro, Minas Gerais
Keywords: Setor sucroenergético; Triângulo Mineiro; Vulnerabilidade territorial; Sugar-energy sector; Territorial vulnerability